Makna spiritualitas dan sosial dalam tradisi mandi kaek pada masyarakat Melayu Jambi - Lutfi Sahfitri; Susi Fitria Dewi; Zaky Farid Luthfi; Tetti Eka Purnama (Journal of Education, Cultural and Politics, 2026)
The Mandi Kaek tradition is a cultural heritage of the Jambi Malay community that contains spiritual and social values. This study aims to analyze the implementation of the tradition as well as the meanings of spirituality and social aspects contained within it for the people of Teluk Kuali Village, Tebo Regency. The research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The results show that the Mandi Kaek tradition is still consistently practiced on the seventh day after birth, maintaining the core ritual structure, although there have been adaptations in location and variations in scale based on the family's economic conditions. The meaning of spirituality is reflected in the recitation of prayers and verses as an expression of gratitude, an effort for the baby's spiritual protection, and the inner experience of the parents. The social meaning is evident in the tradition's function as an official announcement of a new community member, a space for interaction and strengthening social ties, and the affirmation of the principle of reciprocity in community life. The Mandi Kaek tradition serves as a social glue that strengthens the cohesion and collective identity of the Jambi Malay community amidst changing times.